PENGARUH RISIKO KREDIT, RISIKO PASAR DAN RISIKO LIKUIDITAS TERHADAP KINERJA KEUANGAN PERBANKAN (Studi pada Bank Umum Konvensional yang terdaftar di Bursa Efek Indonesia periode 2014-2018) - Natalia Desiko (Journal Competency of Business, 2020)
This study aims to determine the effect of credit risk on the financial performance of banks, the effect of market risk on bank financial performance, the effect of liquidity risk on bank financial performanc. The research method used in this is a quantitative method. The population observed in this study was all conventional cemmercial banks listed on the idx for the period 2015 to 2018. The population in this study was 42 banking companies sampling techniques with a total sample of 56. The type of data used is secondary data. The results showed that Credit Risk (NPL) no significant positive effect on finanial performance (ROA), Market Risk (NIM) has a significant positive effect on bank financial performance (ROA). Liquidity Risk (LDR) has a significant positive effect on bank financial performance (ROA). Credit risk (NPL), market risk (NIM) and liquidity risk (LDR) have different effects. Because seen by the t test, where there are variables that cannot be seen.